2019
DOI: 10.1111/jipb.12755
|View full text |Cite
|
Sign up to set email alerts
|

OS1 functions in the allocation of nutrients between the endosperm and embryo in maize seeds

Abstract: Uncovering the genetic basis of seed development will provide useful tools for improving both crop yield and nutritional value. However, the genetic regulatory networks of maize (Zea mays) seed development remain largely unknown. The maize opaque endosperm and small germ 1 (os1) mutant has opaque endosperm and a small embryo. Here, we cloned OS1 and show that it encodes a putative transcription factor containing an RWP‐RK domain. Transcriptional analysis indicated that OS1 expression is elevated in early endos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Furthermore, interactions between the embryo and endosperm were discovered by transcriptomics analysis in maize, and in particular categories of genes such as transmembrane transporters, including lipid transporters, are enriched in the scutellar aleurone layer and endosperm adjacent to the scutellum (Doll et al ., 2020). It has been reported that maize OPAQUE ENDOSPERM AND SMALL GERM 1 (OS1), a putative TF containing an RWP‐RK domain, functions as a direct or indirect regulator of genes related to resource transportation or allocation between the embryo and endosperm in maize (Song et al ., 2019); however, the specific mechanisms underlying the connection between endosperm and embryo development regulated by OsLFR are unknown. In future work, these hypotheses will be tested with OsLFR complementation driven by embryo‐specific or endosperm‐specific promoters, which might provide more information regarding the exact molecular function of OsLFR .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, interactions between the embryo and endosperm were discovered by transcriptomics analysis in maize, and in particular categories of genes such as transmembrane transporters, including lipid transporters, are enriched in the scutellar aleurone layer and endosperm adjacent to the scutellum (Doll et al ., 2020). It has been reported that maize OPAQUE ENDOSPERM AND SMALL GERM 1 (OS1), a putative TF containing an RWP‐RK domain, functions as a direct or indirect regulator of genes related to resource transportation or allocation between the embryo and endosperm in maize (Song et al ., 2019); however, the specific mechanisms underlying the connection between endosperm and embryo development regulated by OsLFR are unknown. In future work, these hypotheses will be tested with OsLFR complementation driven by embryo‐specific or endosperm‐specific promoters, which might provide more information regarding the exact molecular function of OsLFR .…”
Section: Discussionmentioning
confidence: 99%
“…In maize, the BETL is crucial for uptake and allocation of nutrients from maternal tissues to filial tissues of endosperm and embryo. OPAQUE ENDOSPERM AND SMALL GERM 1(OS1) encodes a putative transcription factor with an RWP-RK domain (Song et al, 2019). It is expressed especially in BETL, conducting zone, and central starch endosperm cells.…”
Section: Dependence Of Embryo Development On Endospermmentioning
confidence: 99%
“…Importantly, GLBs can be employed as a powerful reporter for studying intra-kernel nutrient reallocation. Examination of GLB accumulation can be used to analyze uncharacterized and characterized mutants, for example, opaque11 (also called zhoupi), shohai1, and opaque-endosperm small germ1, all of which have an impaired endosperm-embryo interface (Grimault et al, 2015;Feng et al, 2018;Mimura et al, 2018;Song et al, 2018). Furthermore, it will be interesting to investigate through stacking of aRNAi and bige1 how protein reallocation from the endosperm to embryo impacts the BIGE1 and CYP78A pathways (Suzuki et al, 2015).…”
Section: Glb1 Functions As a Valuable Responsive Marker For Protein Amentioning
confidence: 99%